2022
DOI: 10.3390/ijerph19138020
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessed Aspects of Health 3 Months after COVID-19 Hospitalization—A Swedish Cross-Sectional Study

Abstract: It is not yet fully understood how the patients self-assess their overall health in the early recovery after COVID-19 and if certain patient groups are more prominent in perceived long-time effects of COVID-19. The aim of this study was to describe self-assessed aspects of health in body function, activity and participation 3 months after hospitalization due to COVID-19 and identify difference between groups depending in age, sex and level of hospital care. This cross-sectional study consists of self-assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…On the other hand, the evaluation of 226 COVID-19 survivors from Belgium 3 and 12 months after hospital discharge showed that female sex was associated with the risk of persistent cognitive impairment but not fatigue (Lorent et al, 2022). No sex differences related to the post-COVID fatigue were also found in recent studies assessing Swiss (Larsson et al, 2022) and Swedish populations (Diem et al, 2022). Moreover, to date, only few studies have presented details on the course of fatigue after COVID-19, separately in women and men.…”
Section: Introductionsupporting
confidence: 71%
“…On the other hand, the evaluation of 226 COVID-19 survivors from Belgium 3 and 12 months after hospital discharge showed that female sex was associated with the risk of persistent cognitive impairment but not fatigue (Lorent et al, 2022). No sex differences related to the post-COVID fatigue were also found in recent studies assessing Swiss (Larsson et al, 2022) and Swedish populations (Diem et al, 2022). Moreover, to date, only few studies have presented details on the course of fatigue after COVID-19, separately in women and men.…”
Section: Introductionsupporting
confidence: 71%
“…For the current study, a purposive sampling from the GOT-LOCO cohort was applied to recruit persons who had been discharged from hospital approximately 6 months previously, were 18–65 years old (working age) and who had persisting self-reported symptoms at a previously performed 3-month follow-up (part of the GOT-LOCO study), including respiration, mental health and functional status. The 3-month follow-up was a structured interview, using patient-reported outcome measures, conducted by phone ( 22 ). An invitation letter was sent to 21 persons based on the inclusion criteria, in order to achieve a heterogeneous sample based on age, sex, educational level, employment category and country of birth.…”
Section: Methodsmentioning
confidence: 99%
“…To capture the current aim, participants were purposively selected to generate a heterogeneous sample from the GOT-LOCO cohort, based on the following criteria: approximately 1 year after hospital discharge, people of varying age within the category “working age” (18–65 years old), both men and women, different levels of education, diversity in hospital care including length of stay and diversity of symptoms reported at the 3-month follow-up ( 17 ). Fourteen persons were contacted by an invitation letter followed by a phone call.…”
Section: Methodsmentioning
confidence: 99%